On wetting characteristics of droplet on a spherical particle in film boiling regime - Mitra, S.; Thi, B.; Doroodchi, E.; Pareek, Vishnu; Joshi, J.; Evans, G. (Pergamon, 2016)
This study reports droplet-particle interaction of size ratio less than unity in the film boiling regime on a highly thermally conductive spherical particle surface. Specifically, the effects of impact Weber number (We) of subcooled state droplets comprising water (We=3.9–103.6) and isopropyl alcohol (IPA) (We=8.6–194.6) were studied using high speed imaging technique in the particle temperature range of 250–350 °C. In general, non-wetting interaction behaviour was observed with two distinct outcomes – rebound and complete disintegration demarcated by a critical Weber number range instead of a single threshold value. Extent of surface wetting was characterised by the maximum droplet spread diameter parameter which was found to scale with impact Weber number in a power law form which agrees with the theoretical scaling argument. Additionally, an energy balance model was developed to compute this parameter which provided good agreement with the experimental measurements in the lower Weber number regime, however, higher deviations were noted near the transition regime. Also quantified from experiments was the droplet-particle contact time which exhibited a power law dependency on Weber number in the rebound regime, however, was noted to be almost independent of Weber number in the disintegration regime. Particle surface wettability was characterised by the experimentally measured dynamic contact angles which were found to vary in the range of 120–160o in low Weber number regime manifesting the hydrophobic nature of particle surface in film boiling regime. Also, all the parameters such as contact line velocity, particle temperature and droplet size apparently had relatively insignificant influence on the variation of dynamic contact angle. Temporal variation of non-dimensional spreading parameter exhibited a self-similar behaviour wherein all data collapsed on a single power law profile. It was further shown that the behaviour could also be described by a recovery type exponential profile through suitable non-dimensionalization and both profiles can be utilized to produce a spreading kinetics.